Brain area‐specific diurnal and photic regulation of val‐opsinA and val‐opsinB genes in the zebrafish. (17th March 2015) - Hang, Chong Yee; Kitahashi, Takashi; Parhar, Ishwar S.
Abstract Zebrafish possess two isoforms of vertebrate ancient long (VAL)‐opsin, val‐opsinA (valopa) and val‐opsinB (valopb), which probably mediate non‐visual responses to light. To understand the diurnal and light‐sensitive regulation of the valop genes in different cell groups, the current study used real‐time quantitative PCR to examine the diurnal changes of valopa and b mRNA levels in different brain areas of adult male zebrafish. Furthermore, effects of the extended exposure to light or dark condition, luminous levels and the treatment with a melatonin receptor agonist or antagonist on valop transcription were examined. In the thalamus, valop mRNA levels showed significant diurnal changes; valopa peaked in the evening, while valopb peaked in the morning. The diurnal change of valopa mRNA levels occurred independent of light conditions, whereas that of valopb mRNA levels were regulated by light. A melatonin receptor agonist or antagonist did not affect the changes of valop mRNA levels. In contrast, the midbrain and hindbrain showed arrhythmic valop mRNA levels under light and dark cycles. The differential diurnal regulation of the valopa and b genes in the thalamus and the arrhythmic expression in the midbrain and hindbrain suggest involvement of deep brain VAL‐opsin in time‐ and light‐dependent physiology. <boxed-text content-type="graphic" id="jnc13084-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We show diurnal expression changes of vertebrate ancient long (VAL) opsin genes (valopa and valopb), depending on brain area, time of day and light condition, in the adult male zebrafish. Differential regulation of the valop genes in the thalamus and arrhythmic expression in the midbrain and hindbrain suggest their involvement in time‐ and light‐dependent physiology to adjust to environmental changes.